Pengaruh lingkungan kerja dan stres kerja terhadap kinerja karyawan pada dinas lingkungan hidup kota Semarang - Sukma Ariasa Yulianti; Lie Liana (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This research aims to determine the effect of the work environment and work stress on employee performance at the Semarang City Environmental Service Office. The population in this study were all employees at the Semarang City Environmental Service Office. in this saturated sampling/census sampling, which is the technique of determining the sample if the population members are used as the sample sample in this study as many as 100 people. The analytical tool used in this research is multiple linear regression analysis. research results can be concluded that: (1) the influence of the work environment has a positive and significant effect on employee performance of 0.336 with a value of 0.003 <0.05. then the work environment hypothesis is accepted. (2) the effect of work stress has a negative and insignificant effect on employee performance of -0.012 with a valuesignificant 0.910 > 0.05. then the work stress hypothesis is rejected.